Phosphoinositide 3′-Kinase γ Facilitates Polyomavirus Infection - Paul Clark; Gretchen V. Gee; Brandon S. Albright; Benedetta Assetta; Ying Han; Walter J. Atwood; Daniel DiMaio (Viruses, 2020)
Polyomaviruses are small, non-enveloped DNA tumor viruses that cause serious disease in immunosuppressed people, including progressive multifocal leukoencephalopathy (PML) in patients infected with JC polyomavirus, but the molecular events mediating polyomavirus entry are poorly understood. Through genetic knockdown approaches, we identified phosphoinositide 3′-kinase γ (PI3Kγ) and its regulatory subunit PIK3R5 as cellular proteins that facilitate infection of human SVG-A glial cells by JCPyV. PI3Kα appears less important for polyomavirus infection than PI3Kγ. CRISPR/Cas9-mediated knockout of PIK3R5 or PI3Kγ inhibited infection by authentic JCPyV and by JC pseudovirus. PI3Kγ knockout also inhibited infection by BK and Merkel Cell pseudoviruses, other pathogenic human polyomaviruses, and SV40, an important model polyomavirus. Reintroduction of the wild-type PI3Kγ gene into the PI3Kγ knock-out SVG-A cells rescued the JCPyV infection defect. Disruption of the PI3Kγ pathway did not block binding of JCPyV to cells or virus internalization, implying that PI3Kγ facilitates some intracellular step(s) of infection. These results imply that agents that inhibit PI3Kγ signaling may have a role in managing polyomavirus infections.